Analysis of amino acids and acylcarnitines profiles in small, appropriate, and large for gestational age neonates. (1st February 2022) - Liu, Qian; Yin, Aihua; Wen, Shen; Shi, Xiaomei; Fang, Liyuan; Rao, Tengzi; Liang, Jinqun; Wu, Jing
Abstract: Objective: To identify the amino acid (AA) and acylcarnitines (ACs) profiles in dry blood spot (DBS) of small, appropriate and large for gestational age neonates, and to investigate the difference AA and AC profiles in groups. Methods: Eight thousand nine hundred and fourteen healthy singleton newborns were divided into three groups: small for gestational age (SGA) ( n  = 713), appropriate for gestational age (AGA) ( n  = 7866), and LGA ( n  = 335). Electrospray ionization tandem mass spectrometry was taken to evaluate the concentrations of 11 AAs and 31 ACs in DBS specimens obtained from all enrolled neonates. Results: Compared with the AGA neonates, except propionylcarnitine, the concentrations of SGA neonatal most AAs and AC in the newborn were higher, while those of the newborns in the LGA group were lower. Conclusion: Different concentrations of AAs and ACs in the three groups suggest that SGA may be associated with under anabolic metabolism, while LGA may be associated with over anabolic metabolism.